2021
DOI: 10.1371/journal.pone.0257972
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of HLX10 PD-1 receptor recognition, a promising anti-PD-1 antibody clinical candidate for cancer immunotherapy

Abstract: Cancer immunotherapies, such as checkpoint blockade of programmed cell death protein-1 (PD-1), represents a breakthrough in cancer treatment, resulting in unprecedented results in terms of overall and progression-free survival. Discovery and development of novel anti PD-1 inhibitors remains a field of intense investigation, where novel monoclonal antibodies (mAbs) and novel antibody formats (e.g., novel isotype, bispecific mAb and low-molecular-weight compounds) are major source of future therapeutic candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Serplulimab exhibited a higher affinity to human PD-1 than nivolumab and pembrolizumab, as well as a greater potency to block PD-L1 and PD-L2 signaling than nivolumab . In the in vivo models, serplulimab inhibited tumor growth at a lower dose than nivolumab . The mechanisms underlying the better survival outcome with serplulimab remain unknown, while the preclinical findings provide directions for future studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Serplulimab exhibited a higher affinity to human PD-1 than nivolumab and pembrolizumab, as well as a greater potency to block PD-L1 and PD-L2 signaling than nivolumab . In the in vivo models, serplulimab inhibited tumor growth at a lower dose than nivolumab . The mechanisms underlying the better survival outcome with serplulimab remain unknown, while the preclinical findings provide directions for future studies.…”
Section: Discussionmentioning
confidence: 97%
“…Serplulimab binds to different epitopes in PD-1 compared with nivolumab and pembrolizumab . Serplulimab exhibited a higher affinity to human PD-1 than nivolumab and pembrolizumab, as well as a greater potency to block PD-L1 and PD-L2 signaling than nivolumab .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, functional assays demonstrated that hsa_circ_0081069 silencing impaired cell proliferation, migration and invasion, as well as the angiogenic potential of CRC cells, indicating that hsa_circ_0081069 serves as an indispensable oncogenic factor in CRC. Angiogenesis is an important process for tumor growth and metastasis 37,38 . The growth and survival of a rapidly‐growing tumor population depends on neovascularization to supply oxygen and nutrients 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is an important process for tumor growth and metastasis. 37 , 38 The growth and survival of a rapidly‐growing tumor population depends on neovascularization to supply oxygen and nutrients. 39 As Qian et al showed, miR‐143 suppresses the proliferation and angiogenesis in CRC, which promotes the chemosensitivity to oxaliplatin administration.…”
Section: Discussionmentioning
confidence: 99%
“…Serplulimab (HLX10) is a fully humanized, selective immunoglobulin G4 monoclonal antibody against PD-1 receptor 17 . Serplulimab showed promising antitumor activity and a manageable safety profile in various tumor types in phase 2 clinical trials 18 , 19 .…”
Section: Mainmentioning
confidence: 99%